Australian public sector information: a case study into information practices. Issue 1 (2nd January 2016) - Henninger, Maureen
Abstract: There is much rhetoric and policy in democratic governments concerning the need for public access to government information, and in Australia this access is deemed to be the default position. Such policies run parallel with trends for disseminating this information almost exclusively on departmental and government agencies' websites. This article uses a case-study approach to examine a particular government department's compliance with the regulatory environment and to explore why a particular set of government documents, mandated to be available at a government department website, appeared not to be there. The research demonstrates not only the need for a coherent set of information practices within government departments and based on best practice, but highlights the importance of national libraries' preservation initiatives such as the Australian Government Web Archive.